Permodelan Materi Pengajaran Mata Kuliah Ergonomi pada Program Product Design Engineering - Erwin Rezasyah; Reiko Sarah Pradita; Maria Annissa Laetitia Vheran Loekitodisastro; Calista Angeline; Dave Mangindaan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
The subject of Ergonomics serves as an important part on the education for Product Design Engineering, in which it sets the fundamental understanding for future engineers over the human aspect in engineered a new product. The teaching method of Ergonomics using theoretical approach, followed by laboratory practice to simulate the approach on improving a product or system from the human point of view as user. However, in the context of Product Design Engineering that seeks an output in form of a product solution the approach used in Ergonomics teaching may not be reaching the level of prototyping that can represent a tangible solution. This paper is discussing an alternate approach of applying Project-based model for teaching Ergonomics with aim to produce an output of conceptual product to materialize the Ergonomics improvement parameters resulted from the theoretical and laboratory practice approach initially conducted from the previous approach. The adoption of Design Thinking method into the teaching plan was being introduced as a mean of allowing a direct and practical way of leading the process up to prototyping phase and thus setting up a platform for further improvement. The case study was deducted from the teaching subject of Human-Integrated Systems class by utilizing the ongoing teaching plan as the media for introducing the new approach.